Overexpression of Striated Muscle Activator of Rho Signaling (STARS) Increases C2C12 Skeletal Muscle Cell Differentiation - Wallace, Marita A.; Della Gatta, Paul A.; Ahmad Mir, Bilal; Kowalski, Greg M.; Kloehn, Joachim; McConville, Malcom J.; Russell, Aaron P.; Lamon, Séverine (Frontiers in Physiology, 2016)
Background: Skeletal muscle growth and regeneration depend on the activation of satellite cells, which leads to myocyte proliferation, differentiation and fusion with existing muscle fibres. Skeletal muscle cell proliferation and differentiation are tightly coordinated by a continuum of molecular signalling pathways. The striated muscle activator of Rho signalling (STARS) is an actin binding protein that regulates the transcription of genes involved in muscle cell growth, structure and function via the stimulation of actin polymerization and activation of serum-response factor (SRF) signalling. While STARS mediates cell proliferation in smooth and cardiac muscle models; however, whether STARS overexpression enhances cell proliferation and differentiation has not been investigated in skeletal muscle cells. Results: We demonstrate for the first time that STARS overexpression enhances differentiation but not proliferation in C2C12 mouse skeletal muscle cells. Increased differentiation was associated with an increase in the gene levels of the myogenic differentiation markers Ckm, Ckmt2 and Myh4, the differentiation factor Igf2 and the myogenic regulatory factors (MRFs) Myf5 and Myf6. Exposing C2C12 cells to CCG-1423, a pharmacological inhibitor of SRF preventing the nuclear translocation of its co-factor MRTF-A, had no effect on myotube differentiation rate, suggesting that STARS regulates differentiation via a MRTF-A independent mechanism. Conclusion: These findings position STARS as an important regulator of skeletal muscle growth and regeneration.